Influencia de la fecha de siembra y frecuencia de corte sobre el rendimiento y digestibilidad de mijo perla, Pennisetum typhoides y sorgo azucarado, Sorghum saccharatum - Gargano, Alfredo O (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
In a factorial experiment, conducted in Bahia Blanca (Province of Buenos Aires, Argentina) pearl millet cv. "Gahi-1" and sweet sorghum ev. "Don Roberto INTA", were compared during three years. Two sowing dates: October 30 and November 20, and three cutting frequencies 50 cm and 80 cm of height and at flowering time were studied. Dry matter yield was higher in sorghum than in pearl millet though differences not always were significant. Sorghum was partially affected by the sowing date but not pearl millet. Dry matter yield increased in both species when cutting frequency decreased. On the other hand, digestibility decreased, more in pearl millet (68%-61.32%- 52.95%) than in sorghum (68,09%-65,08%-60,74%). Digestible dry matter yield had the same trend as dry maiter in sorghum but not in pearl millet. In general, a more satisfactory response was obtained with sorghum than with pearl millet.